(untitled) (Cardiovascular Journal, 2013)
Cardiac rhythm control devices i.e. pacemakers, implantable cardioverter-defibrillators (ICDs) and biventricular pacemakers are at times lifesaving treatment and prevention of arrhythmia. But, despite definite indications, many people in the developing countries cannot afford these devices due to high cost, and succumb to premature death. On the other hand, after implantation, pacemakers and ICDs are sometimes underutilized because of premature explantation due to death of the recipient, device infection, or upgradation, leaving a considerable extent of serviceable battery life unused. Majority of these explanted devices are simply thrown away. Though made for single use, a growing body of evidence indicates the safety, efficacy and feasibility of reimplantation of the prematurely explanted devices in patient in need who is otherwise unable to afford a new one. Patients, physicians, morticians, and even the general public support the idea of device donation and recycling. A number of organizations around the world have engaged themselves in this benevolent effort, and t he feasibility of device reutilization programme has already been established. However, some logistic, legal and ethical concerns are yet to be solved. The statutory bodies and professional organizations should address the issue of device recycling to solve the unsolved issues and formulate standard practice guidelines. In that case, such medical wastes may turn into invaluable resources, and help ensuring equitable medical care throughout the world. Cardiovascular Journal Volume 6, No. 1, 2013, Page 52-59 DOI: http://dx.doi.org/10.3329/cardio.v6i1.16116